2022
DOI: 10.3399/bjgp.2021.0512
|View full text |Cite
|
Sign up to set email alerts
|

Resident and early-career family physicians’ focused practice choices in Canada: a qualitative study

Abstract: Background: Although focused practice within family medicine may be increasing globally, there is limited research on the factors contributing to decisions to focus practice. Aim: We aimed to examine the factors influencing resident and early-career family physician choices of focused practice across three Canadian provinces. Design and Setting: We analyzed a subset of qualitative interview data from a study across British Columbia, Ontario, and Nova Scotia. Method: A total of 22 resident family physicians and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 23 publications
0
29
0
3
Order By: Relevance
“…24 The reasons for shifts away from comprehensive primary care are numerous and complex. Early results from Canadian research have shown they include: 9,25 Lack of the interprofessional team-based supports necessary to respond to trends in older patient age, increasing patient complexity independent of age, and increasing complexity in managing chronic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…24 The reasons for shifts away from comprehensive primary care are numerous and complex. Early results from Canadian research have shown they include: 9,25 Lack of the interprofessional team-based supports necessary to respond to trends in older patient age, increasing patient complexity independent of age, and increasing complexity in managing chronic diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions to FP workforce shortages identified in the literature focus on addressing deterrents to the practice of comprehensive primary care, including perceived poor respect for primary care as a profession, inadequate compensation, and inadequate administrative and interdisciplinary health supports to manage increasing patient complexity. 22,[41][42][43] Our finding of a shift toward APP models underscores the desire among comprehensive FPs for financial stability and teambased supports. Further, we identified large numbers of patients with chronic diseases and complex social needs, all of which are highly amenable to team-based care.…”
Section: Discussionmentioning
confidence: 98%
“…1,16–21 Rather, primary care physicians increasingly favor episodic care settings, such as walk-in clinics, 6 and focused scopes of practice, such as sports medicine or hospitalist care. 22–27 Moreover, the concentration of women in primary care may further reduce capacity, with research finding women spend more time with patients 28 and receive more patient requests than men. 29,30…”
Section: Introductionmentioning
confidence: 99%
“…Within the Canadian context, Myhre et al [ 66 ] identified that geographic factors (e.g. rural location, community size, distance to a large hospital), personal physician characteristics, professional education, and patient factors influenced scope of practice, while Kabir et al [ 67 ] discovered that training, organisational structure, inadequate remuneration, workload, professional satisfaction, and the amount of patient care required per treatment influenced scope of practice. Additionally, Myles et al [ 68 ] reported that geography, the practice environment, the needs of those within communities, and regional and jurisdictional variations in healthcare delivery were key elements in determining scope of practice of family physicians in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%